PENERAPAN TEKNOLOGI SONIC BLOOM DAN PUPUK ORGANIK UNTUK PENINGKATAN PRODUKSI BAWANG MERAH (Studi Kasus Bawang Merah di Brebes, Jawa Tengah) - Yulianto Yulianto (Universitas Tadulako, 2008)
The objective of this research was to evaluate the potential ability of sonic bloom technology and organic fertilizer application on shallot production. The experiment was arranged in a split-plot design. The organic fertilizer application was the main plot while the sub-plot was the sonic bloom application. The shallot variety Kuning was used at this experiment. The experimental results indicated that the sonic bloom and organic fertilizer application increased the shallot yield. The highest yield was found in the sonic bloom and organic fertilizer combination, followed by the sonic bloom, and the organic fertilizer treatments. The yield of shallot applied with sonic bloom and organic fertilizer was 26.43 t ha-1. The yield of shallot applied with sonic bloom, organic fertilizer, and the control were 23.39, 21.98, and 19.58 t ha-1, respectively. MBCR of sonic bloom and organic fertilizer combination, sonic bloom, and organic fertilizer applications were 8.05, 6.91, and 5.73, respectively.